Relasi Parasosial sebagai Strategi Komunikasi Pemasaran dalam Live Commerce TikTok di Indonesia - Zahrotul Munawwaroh; Reza Mehdi Fauzi; Mohammad Syarrafah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
TikTok Live phenomenon in Indonesia has created a new form of interaction between sellers and audiences through hosts who blend entertainment and real-time product promotion. This study examines the marketing communication strategies employed by “Mas Farhan Batik,” a prominent TikTok Live host known for selling batik products while cultivating strong emotional bonds with his viewers. Using a qualitative case study approach and content analysis, this research investigates how parasocial elements are constructed and strategically leveraged to foster consumer engagement and trust in a live commerce context. Findings reveal that personalized, narrative-driven, and consistent communication enhances psychological proximity between host and audience. Specifically, elements such as the illusion of intimacy, emotional involvement, pseudo-interaction, and perceived authenticity act as key mechanisms for building a sense of belonging and driving impulse buying behavior. The study also highlights the role of everyday influencers in replacing celebrity endorsements, offering a more authentic and affective communication channel that resonates deeply with target consumers. These insights contribute to the theoretical development of parasocial interaction in interactive digital marketing and suggest that emotionally resonant communication strategies can significantly enhance brand loyalty and sales conversion in the emerging ecosystem of Indonesian live commerce.